Проблеми призначення покарання неповнолітнім - Чупринський, Б.; Chuprynskyi, B. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проведено науковий аналіз проблем призначення покарання неповнолітнім особам, особливості застосування ст. 98 КК України. Аналізується неповнолітній вік суб’єкта злочину як обставини, що пом’якшує покарання. Зазначається про недопустимість подвійного врахування пом’якшуючої обставини при призначенні покарання. Наголошується про диференційовані види і строки покарань, які можуть призначатися неповнолітнім. Розглядається молодий вік суб’єкта злочину як обставина, що пом’якшує покарання.The article provides scientific analysis of the challenges concerning the imposition of punishment on the juvenile delinquents, the application of Art. 98 of the Criminal Code of Ukraine peculiarities. The author argues that the juvenile age of the subject of a crime is a circumstance mitigating punishment. The study brings to the conclusion that in sentencing a juvenile court must take into account the age of the subject of a crime and consider it as a factor that mitigates punishment but not ignore it. Since the mitigating circumstances are included into the norms of not only Special but also the General Part of the Criminal Code, they must not be re-applied with respect to the matters of criminal liability. Thus, nonage of the offender ought to be taken into account as a factor that mitigates liability in all cases where special norms for juveniles are not provided. Analysis of the judicial practice shows that when sentencing court takes into account the young age of the person who has not reached adulthood as a factor that mitigates verdict. In the Criminal Code of Ukraine legislator also differentiates types and terms of punishment that can be administered for the underaged and adults. The list of penalties specified in Art. 98 of the Criminal Code of Ukraine is exhaustive, other basic or additional penalties are not applicable to the minors, even if in the of course of the court proceedings they reached their adulthood.
Problems of Sentencing Juvenile Delinquents
Keywords: неповнолітні, злочин; суд; призначення покарання; види покарань; обставини які пом’якшують та обтяжують покарання; juvenile; crime; court; imposition of punishment; penalties